HUKUMAN UNTUK PENDISIPLINAN PESERTA DIDIK DALAM DUNIA PENDIDIKAN PERSPEKTIF PSIKOLOGI DAN MAQASID SYARIAH - Agus Basuki (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2022)
Abstract Physical punishment in education is considered effective in teaching discipline and responsibility to children. In addition to providing a deterrent effect, corporal punishment is considered to provide learning about norms that should not be violated and must be obeyed in life. However, corporal punishment turns out to have an impact on children's physical and psychological, so there are limitations that must be adhered to in giving corporal punishment. Law Number 17 of 2016 concerning Child Protection states that corporal punishment can be categorized as violence against children. So the question arises how to apply corporal punishment to children in education by examining Islamic criminal law thinking. This research uses qualitative methods with juridical, normative and psychological approaches. The results of the study stated that psychologically corporal punishment in education does not exist, but corporal punishment can still be implemented in education by considering the child's age, physical and psychological conditions when receiving punishment, errors and punishments are interrelated, implemented as soon as possible, leaving no scars, give the child an understanding of the mistakes made and that punishment is given as a last resort. According to Islamic criminal law, corporal punishment is included in the category of acts of persecution that can be charged with qisas punishment. Keywords : corporal punishment, education, Islamic criminal law, pshychology.